Determining the Effects of Manganese Source and Level in Diets Containing High Levels of Copper on Growth Performance of Growing-Finishing Pigs - H. R. Kerkaert; J. C. Woodworth; J. M. DeRouchey; S. S. Dritz; M. D. Tokach; R. D. Goodband; N. E. Manzke (Kansas Agricultural Experiment Station Research Reports, 2020)
A total of 1,994 pigs (PIC; 337 × 1050; initially 88.2 lb) were used to determine the effect of manganese (Mn) source and level on finishing pig growth performance. This experiment was a follow-up to an Mn source by level study conducted last year. However, unlike last year’s study, in the present study all diets contained 150 ppm added Cu from Cu hydroxychloride (IBC; Micronutrients, Indianapolis, IN). Dietary treatments were arranged in a 2 × 3 factorial with main effects of Mn source (Mn hydroxychloride, IntelliBond M, Micronutrients, Indianapolis, IN; or Mn sulfate, MnSO4, Eurochem, Veracruz, Mexico), and increasing added Mn concentration (8, 16, and 32 ppm). The trace mineral premix was formulated without added Mn. There were 27 pigs per pen and 12 pens per treatment. Diets were corn-soybean meal-distillers dried grains with solubles-based and were fed in 4 phases. Overall, there was no (P>0.10) Mn source × level interaction observed for average daily gain (ADG), average daily feed intake (ADFI), and feed efficiency (F/G). Pigs fed IBM had increased (P<0.05) final body weight (BW), ADG, and ADFI compared to pigs fed MnSO4. Pigs fed 16 ppm of Mn tended (P = 0.088) to have reduced ADFI when compared to pigs fed 8 and 32 ppm of Mn. In conclusion, there appears to be little benefit in growth performance by feeding more than 8 ppm of added Mn. However, pigs fed IBM had improved growth performance compared with those fed MnSO4. This response is different than our previous study with identical Mn sources but without high levels of added Cu. Further research is needed to understand why we observed an Mn source difference to Mn hydroxychloride when fed in conjunction with pharmacological levels of Cu on pig growth performance.
Keywords: copper; finishing pig; growth; manganese; manganese hydroxychloride